Psychological defenses and coping strategies in preschool children: sex differences and relationship with psychological health - Kuftyak, Elena (Social Welfare: Interdisciplinary Approach, 2020)
The article represents the research, analysed the reviewing of defensive mechanisms and coping strategies in the context of the mental health of pre-school children of different gender. The results obtained through study point to differentiation of psychological defence and coping strategies mechanisms based on gender and the condition of mental health. It is revealed that mentally healthy pre-school age children prefer to use effective and socially upheld coping-strategies, which reduce the pressure through socially upheld behaviour patterns (e.g., through the decent “children’s activity” – play, walk and etc.).  Mentally healthy girls more often focus on overcome the difficulties within themselves. Boys, who have emotional symptoms, as usual prefer the destructive emotional expression strategy, that lets to ease the tension. Boys with the low level of anxiety are oriented to the passive distraction, while girls focus on the social contacts.  Received results can be used for development of psychological prevention of mental health offences programmes
Keywords: psychological defenses; coping behavior; gender differences; psychological health; preschool children